Efficient access of replicated data in distributed database systems - Mat Deris, Mustafa (2001)
Replication is a useful technique for distributed database systems where a data object will be accessed (Le., read and written) from multiple locations such as from a local area network environment or geographically distributed world wide. This technique is used to provide high availability, fault tolerance, and enhanced performance. This research addresses the performance of data replication protocol in terms of data availability and communication costs. Specifically, this thesis present a new protocol called Three Dimensional Grid Structure (TDGS) protocol, to manage data replication in distributed database systems (DDS). The TDGS protocol is based on the logical structure of sites/serquorum in the DDS. The protocol provide high availability for read and write operations with limited fault-tolerance at low communication cost. With TDGS protocol, a read operation is limited to two data copies, while a write operation is required with minimal number of copies. In comparison to other protocols, TDGS requires lower communication cost for an operation, while providing higher data availability . A system for building reliable computing over TDGS Remote Procedure (TDGSRP) system has also been described in this research. The system combines the replication and transaction techniques and embeds these techniques into the TDGS-RP system. The model describes the models for replicas, TDGS-RP, transactions, and the algorithms for managing transactions, and replicas.